Hydroxyapatite paste Ostim®, without elevation of full‐thickness flaps, improves alveolar healing stimulating BMP‐ and VEGF‐mediated signal pathways: an experimental study in humans. (15th December 2011) - Canuto, R. A.; Pol, R.; Martinasso, G.; Muzio, G.; Gallesio, G.; Mozzati, M.
Abstract: Objective: Tooth extraction is considered as the starting point of jaw atrophy via osteoclast activity stimulation. The maintenance of dental alveolar bone depends on surgery procedure and use of materials to maintain prior space favoring bone regeneration. Among substitutes used in dentistry to fill bone defects, Ostim‐Pastes (Ostim ® ) is a nanocrystalline paste tested for treatment of severe clinical conditions. This research first investigated the effect of Ostim on alveolar healing, comparing in the same healthy subjects, an Ostim ® ‐filled socket with a not‐filled one. Moreover, it also proposed a new surgical protocol for the post‐extractive socket treatment using the graft materials without elevation of full‐thickness flaps. Material and methods: Fourteen patients were enrolled to bilateral maxillary or mandibular extraction that was performed without elevation of full‐thickness flaps. In each patient, one socket was filled using Ostim ®, and the other one was allowed to undergo natural healing. No suture was carried out. Clinical and biologic parameters were screened at 1, 7, and 14 days. Results: Obtained results evidenced that nanocrystalline hydroxyapatite supports bone regeneration, increasing the synthesis of pro‐osteogenic factors as bone morphogenetics protein (BMP)‐4, BMP‐7, alkaline phosphatase, and osteocalcin. Moreover, filling post‐extractive socket with nanocrystalline hydroxyapatite paste leads to a complete epithelialization already at 7 days after extraction, despite the fact that the teeth were extracted without elevation of full‐thickness flaps . The improved epithelialization is mediated by increased vascular endothelial growth factor (VEGF) expression. No significant change was observed in inflammatory parameters, with exception of an early and transient IL‐1β induction, that could trigger and improve alveolar healing. Conclusions: Clinical and biomolecular observations of this explorative study evidenced that nanocrystalline hydroxyapatite improves alveolar socket healing, increasing angiogenesis, epithelialization, and osteogenesis, also in absence of elevation of full‐thickness flaps.